Cartilage Restoration: Microfracture and Osteochondral Autograft Transplantation - Redondo, Michael L.; Beer, Adam J.; Yanke, Adam B. (The Journal of Knee Surgery, 2018)
The treatment of patellofemoral cartilage defects presents several distinct challenges when compared with cartilage restoration techniques used for other compartments of the knee due to the unique anatomy and distribution of forces. The etiologies of patellofemoral articular cartilage lesions include acute traumatic instability injuries, such as dislocation and subluxation, osteochondritis dissecans, and chronic degenerative changes. Regardless of the etiology, untreated patellofemoral cartilage lesions can contribute to activity-limiting anterior knee pain. The goal of patellofemoral cartilage restoration procedures is to impart symptomatic relief and improve quality of life by repairing the articular cartilage surface and any comorbid malalignment or maltracking.Microfracture and osteochondral autograft transplantation (OAT) are two cartilage restoration procedures to consider when treating full-thickness patellofemoral chondral defects. Considered by some experts to be the gold standard therapy, microfracture is one of the most common procedures used for cartilage restoration. The technique involves the perforation of the subchondral bone plate for the release of marrow elements, filling the defect with a fibrocartilage clot repair. Though less commonly used, OAT allows defect replacement with native hyaline cartilage via autologous transplantation from a non-weight bearing area. The purpose of this article is to discuss the indication, technical considerations, and outcomes of microfracture and OAT when used for treating chondral lesions of the patellofemoral joint.
Keywords: microfracture; osteochondral autograft transplantation; cartilage restoration